2021
DOI: 10.1302/0301-620x.103b8.bjj-2021-0021.r1
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Unified Classification System for postoperative periprosthetic femoral fractures around cemented polished taper-slip stems

Abstract: Aims This aim of this study was to assess the reliability and validity of the Unified Classification System (UCS) for postoperative periprosthetic femoral fractures (PFFs) around cemented polished taper-slip (PTS) stems. Methods Radiographs of 71 patients with a PFF admitted consecutively at two centres between 25 February 2012 and 19 May 2020 were collated by an independent investigator. Six observers (three hip consultants and three trainees) were familiarized with the UCS. Each PFF was classified on two sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…16 The classification has been subsequently validated, 25 although its validity and reliability in differentiating loose from fixed cemented polished taper stems has been questioned. 26 The COMPOSE femoral PPF cohort was predominantly UCS type B, 76% hip and 58% knee, in keeping with previous published series of PPFs around hip arthroplasty where the reported incidence of B type fractures ranged from 70% to 78%, 27,28 and with Swedish registry data (86%). 13 Type A fractures are often under-reported or excluded from cohort studies examining PPFs as they may be treated nonoperatively and/or be managed in an outpatient setting.…”
Section: Discussionsupporting
confidence: 84%
“…16 The classification has been subsequently validated, 25 although its validity and reliability in differentiating loose from fixed cemented polished taper stems has been questioned. 26 The COMPOSE femoral PPF cohort was predominantly UCS type B, 76% hip and 58% knee, in keeping with previous published series of PPFs around hip arthroplasty where the reported incidence of B type fractures ranged from 70% to 78%, 27,28 and with Swedish registry data (86%). 13 Type A fractures are often under-reported or excluded from cohort studies examining PPFs as they may be treated nonoperatively and/or be managed in an outpatient setting.…”
Section: Discussionsupporting
confidence: 84%
“…For B2 and B3 fractures, the proportions of patients undergoing revision (B2 77%; B3 77%) were lower than the 87% (B2) and 96% (B3) reported in the Cochrane Review by Khan et al 12 The difference in the proportion of patients undergoing revision for B1 and B2/B3 PPFs may to be due to the contemporary use of taper-slip cemented femoral stem designs. 13 The taper-slip stem design requires controlled subsidence within an intact cement mantle and therefore, when the cement-implant interface is broken, the implant is by definition loose and may require revision. In uncemented, proximally well-fixed implants, a fixation alone may be appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…In uncemented, proximally well-fixed implants, a fixation alone may be appropriate. 9,13 National standards for the treatment of hip fragility fractures stipulate that these injuries should be operated on within 36 hours of admission. 14 COMPOSE data demonstrated that for all fractures, the median time between admission and surgery across 27 NHS sites was four days.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, VCS grade was assessed using plain radiographs only. Although the VCS is a well validated, reliable classification system [32][33][34], we acknowledge that stem stability can sometimes only be established intraoperatively, especially for polished taper-slip stems [35]. However, in this retrospective series, intraoperative stability was frequently not recorded.…”
Section: Discussionmentioning
confidence: 82%